A TWELVE-HUNDRED-YEAR STABLE OXYGEN ISOTOPE CHRONOLOGY CONSTRUCTED USING SUBFOSSIL WOOD FROM SCHWARZENSEE LAKE, AUSTRIAN ALPS. Issue 6 (20th December 2022) - Kłusek, Marzena; Grabner, Michael; Pawlyta, Jacek; Pawełczyk, Sławomira
ABSTRACT: This study presents a new stable oxygen isotope chronology, covering the years 800–2000 AD, constructed using modern and subfossil wood derived from trees growing around Lake Schwarzensee in Austria. The climatic signal imparted in the chronology is conditioned mainly by the direct influence of environmental factors on the isotopic signature of source water, which in turn is regulated by evaporation and condensation mechanisms. The second driver of stable oxygen isotope is the physiological response of trees to changing weather conditions, most importantly rates of transpiration. The chronology of stable oxygen isotopes corresponds well with both temperature (r = 0.485; p < 0.05) and total precipitation (r = −0.548; p < 0.05) during the growing season (May–September). This mixed signal results from the fact that the relationship between the content of stable oxygen isotopes and the influence of climate is multifactorial. Moreover, the effect exerted by meteorological conditions on stable isotope ratio changes over time. This is most probably linked to interannual variation in climatic and environmental factors.